Faktor-Faktor Sdm yang Mempengaruhi Kualitas Projek Ti (Human Resource Factors That Impacts It Project’s Quality) - Monica Hidajat; Dian Felita Tanoto (ComTech: Computer, Mathematics and Engineering Applications, 2014)
One of the required resources in IT development projects is the human resource. Human resources has a role and an enormous influence on the process and the success of IT projects. By conducting a literature review and analysis of the factors of human resources, it is obtained the factors that influence the operation of IT projects. The factors may include factors that can be absorbed and factors that cannot be absorbed. Weaknesses in human resources are weaknesses that can be pressed or elaborated in such a way so as not to interfere the performance of the project. Performance of the project is one aspect that determines the quality of a project. The more positive the value of the performance of the project, the more positive the value of the quality of a project.